Analysis of the PAX8 gene in congenital hypothyroidism caused by different forms of thyroid dysgenesis in a father and daughter - (:unkn) unknown (My University, 2004)
Thyroid dysgenesis occurs sporadically with only rare familial presentation. We report a father and daughter with congenital hypothyroidism caused by different forms of thyroid dysgenesis. The father had a severely hypoplastic thyroid gland in a normal location, whereas the daughter had an ectopic thyroid gland in a sublingual position. Her brother had a hypoplastic thyroid but was euthyroid. The involvement of the candidate gene, PAX8, as the cause of thyroid dysgenesis in this family was partially excluded by linkage analysis, and the possibility of a de novo mutation excluded by sequencing.
Keywords: Adult; Female; Humans; Male; DNA-Binding Proteins; Infant, Newborn; Hypothyroidism; Trans-Activators; Pedigree; Radionuclide Imaging; Base Sequence; Thyroid Gland; DNA Primers; Thyroid Function Tests; Nuclear Proteins; Congenital Hypothyroidism; Paired Box Transcription Factors; PAX8 Transcription Factor